Analyst Types of Malpractice In Health Law - Alim Usemahu, Syahdan; Dame Panjaitan, Junifer (International Journal of Social Research, 2024)
Malpractice refers to medical practices that do not comply with the applicable laws and ethical codes. It can also refer to negligence, errors, or a doctor's inability to solve a patient's problem in such a way that the patient is dissatisfied with the outcome. Patients suffer as a result of healthcare workers' neglect of necessary procedures when they lack knowledge of health-related topics. This occurs when medical practices are performed on patients who become victims, but medicine is based on procedures or how doctors perform actions. Whether malpractice occurs or not is not judged by its adverse consequences. The definition of malpractice under current law is unclear. However, the concept of malpractice can be found in Article 11 paragraph 1 letter b, Law No. 6 of 1963 concerning healthcare personnel, which has been repealed and replaced by Law No. 23 of 1992 which regulates healthcare.